2021
DOI: 10.2478/foecol-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Endemic and invasive Coccinellidae associated with maize (Zea mays L.) fields, in Manabi province, Ecuador

Abstract: Maize (Zea mays L.), which is considered an important cereal everywhere, is widely cultivated in different agroecological conditions. Throughout their phenological stages, maize crops are attacked by pests and diseases, and in Ecuador these phytosanitary problems are usually counteracted with applications of pesticides. However, knowledge of beneficial entomofauna is fundamental to guide pest management programs. As part of this objective, the Coccinellidae species present in maize fields in localities (Santa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These two species, along with Ch. sexmaculata, had been recorded as part of the ladybirds associated with corn agroecosystems in the province of Manabí, Ecuador [42]. Similar to what was found in this study, the predator Podisus sp.…”
Section: Discussionsupporting
confidence: 87%
“…These two species, along with Ch. sexmaculata, had been recorded as part of the ladybirds associated with corn agroecosystems in the province of Manabí, Ecuador [42]. Similar to what was found in this study, the predator Podisus sp.…”
Section: Discussionsupporting
confidence: 87%
“…The species L. testaceipes and S. aphidivorus have been found in other field studies in different geographical The species of predatory coccinellids and syrphids found in this study had been previously reported for Ecuador. Bailon et al (2022) in an inventory carried out in three geographical areas of the province of Manabí detected 13 taxa of coccinellids associated with aphids in corn, with Ch. sexmaculata being the most abundant species followed by C. sanguinea and H. convergens.…”
Section: Resultsmentioning
confidence: 99%
“…Small wasps emerged from hoverfly pupae, which were identified using dichotomous keys of Narendran et al (2007) and Xiao et al (2009). Individuals of lady beetles (Coleoptera: Coccinellidae) preying on R. maidis were observed in the field, and were collected into flasks containing 70% ethyl alcohol and the species were identified by comparison with voucher specimens collected in previous studies carried out in the same province (Bailon et al, 2022). Hoverfly adults were identified with the keys of Marinoni et al (2007) and Mengual et al (2018).…”
Section: Methodsmentioning
confidence: 99%